DAMPAK KEGIATAN KEPRAMUKAAN TERHADAP RASA NASIONALISME SISWA DI SMPN 1 GENDING - Masruro, Faizatun (Universitas Islam Zainul Hasan Genggong, 2023)
The general aim of this research is to describe the impact of scouting activities on the sense of nationalism of students at SMPN 1 Gending. The reason the researcher conducted this research was none other than because the researcher wanted to know whether scouting activities really had a good impact on students' attitudes and sense of nationalism or not. This research uses a qualitative descriptive method as its methodology. The research location is at SMPN 1 Gending. Data was obtained from direct observation, interviews and documentation study guidelines as instruments in this research. Data was analyzed through the stages of data collection, data reduction, data presentation and drawing conclusions. The final stage is to test the validity of the data using the Source Triangulation procedure. Source triangulation is carried out to test the credibility of the data by checking data that has been obtained through several sources. The results of the research show that the extracurricular activities carried out at SMPN 1 Gending every Wednesday for interested scouts and on Saturdays for mandatory scouts, really have a good impact on students' attitudes and sense of nationalism. This is reflected in several attitudes, namely, discipline, honesty, courage, willingness to sacrifice and obeying regulations.